ANALISIS DETERMINAN DAN DAYA SAING EKSPOR MINYAK KELAPA SAWIT INDONESIA DI PASAR DUNIA - Alfis Yuhendra; Eliza Eliza; Novia Dewi (Fakultas Pertanian, Universitas Riau, 2017)
Palm oil is the leading agricultural export commodity of Indonesia, which is the biggest palm oil producer and exporter in the world. The size of palm oil plantations increases 3,27-11,33 percent every year. Despite the increased plantation size, Indonesian palm oil export has negative growth with the peak at negative 10,32% in 2013. Compared with the main competitor, the CPO export of Indonesia always beats Malaysia. However, Malaysia leads in refinery and fraction and oleochemical group commodities. This study was aimed to determine factors determining Indonesia palm oil export and its competitiveness in the world market and compared with Malaysia. The observation was performed from 2001 to 2014 on 10 leading importing countries using Gravity Model theory with palm oil export value as the dependent variable and the GDP per capita of Indonesia and the importing countries, geographical distance, population, soy oil price, and RSPO regulation as the independent variables. To determine the competitiveness, the method used here was RCA (Revealed Comparative Advantage) to analyze the comparative competitiveness and Vollrath Index to analyze the competitiveness. The research result showed that Indonesia’s GDP per capital had positive and significant influence on Indonesian palm oil export. Meanwhile, the GDP per capita of importing countries had negative and significant influence on Indonesian palm oil export value. The analysis result of competitiveness revealed that Indonesia’s CPO commodity had comparative and competitive advantages over Malaysia. Refinery and fraction and oleochemical group commodities had similar result. Indonesian commodities had comparative and competitive advantages in the world market but lost the competition with Malaysian commodities.